Características físico-químicas e sensoriais de embutido fresco de aves de descarte preparado com diferentes antioxidantes naturais - Borba, Hirasilva [UNESP]; Scatolini-silva, Aline Mary [UNESP]; Giampietro-ganeco, Aline [UNESP]; Boiago, Marcel Manente; Souza, Pedro Alves [UNESP] (UFBA - Universidade Federal da Bahia, 2012)
The present study evaluated the effect of the use of natural antioxidants in different spent hens processed meat, the physical-chemical and sensory characteristics of product were analyzed. The experiment was conducted at the Technology Laboratory of Animal Products, Department of Technology - FCAV / Unesp - Campus of Jaboticabal. Forty-five laying hens with approximately 80 weeks of age were used, distributed in a completely randomized experimental design in a 4x4 factorial arrangement, 4 condiment types (control, rosemary, clove and oregano, and the last three natural antioxidants) and 4 storage times (0; 3; 6 and 9 days at 4Â°C), with sixteen treatments and tree repetitions. It were evaluated the characteristics of humidity, pH, color, cooking loss, shear force, TBARS number and sensory analyze. The averages were obtained by Tukey test 5% of significance. The results showed an interaction between the storage time and condiments types in all analyzed parameters. It was concluded that oregano use decreased the processed meat oxidation, also pleased the judges in sensory analysis. The lowest notes in sensory analysis were obtained with the treatment that contained clove.

Objetivou-se avaliar o efeito de diferentes antioxidantes naturais em embutidos frescos formulados com carnes provenientes de aves de descarte nas características físico-químicas e sensoriais do produto. O experimento foi realizado no Departamento de Tecnologia - Laboratório de Tecnologia dos Produtos de Origem Animal da FCAV/Unesp - Campus de Jaboticabal. Para tanto, foram utilizadas 45 aves de postura, com aproximadamente 80 semanas de idade, distribuídas em um delineamento inteiramente casualizado em esquema fatorial 4x4, sendo quatro tipos de condimentos (controle, alecrim, cravo-da-índia e orégano) e quatro períodos de armazenamento (zero, três; seis e nove dias a 4Â°C), o que totalizou 16 tratamentos e três repetições. Foram ainda avaliadas as características de umidade, pH, cor, perdas por cozimento, força de cisalhamento, número de TBARS e análise sensorial. As médias obtidas foram comparadas pelo teste de Tukey a 5% de significância. Houve interação entre o período de armazenamento e o condimento utilizado em todas as características avaliadas. O tratamento que continha cravo da Índia foi o que recebeu as menores notas na análise sensorial. A utilização do orégano diminuiu a oxidação do embutido, além de ter agradado os provadores na análise sensorial.
Physical-chemical and sensory characteristics of spent hens meat sausage prepared with different naturals antioxidants
Keywords: armazenamento; carne de frango; qualidade; poultry; quality; storage